Opportunities and Barriers for Entrepreneurship in the Metaverse Age - Karademir, Ömer (IGI Global, 2023)
The metaverse is a 3D (three-dimensional) virtual world synchronized with the real world, where users interact with a digital avatar using augmented reality technologies. The transformative impact of this virtual world is making itself felt in many areas, as are the opportunities and challenges it creates. Entrepreneurs' capacity to foresee these risks and assess opportunities may be crucial to the survival of their businesses in the future. This study aims to examine potential business opportunities, obstacles, and risks for entrepreneurs in the metaverse universe. To this end, studies in the metaverse literature were examined, and as a result of these studies, an attempt was made to determine the potential business opportunities that the metaverse universe could create. As a result, it was found that the metaverse offers very different business opportunities for entrepreneurs in different fields. This study considers it essential for entrepreneurs to invest in the metaverse to evaluate these business opportunities.